EFFECT CASSIA AURICULATA ON LIPID PEROXIDATION AND LIPIDS IN STREPTOZOTOCIN - NICOTINAMIDE INDUCED DIABETIC RATS - Pidaran Murugan, (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: The present study investigated the beneficial effect of Tanner’s cassia Cassia auriculta  flower extract (CFEt) and leaf extract (CLEt) on lipid peroxidation and lipids properties in streptozotocin (STZ) –induced diabetic rats.Methods: The effects of an aqueous extract of CFEt (0.45 g/kg), CLEt (0.45 g/kg) and  glybenclamide on plasma glucose, insulin,  thiobarbituric acid reactive substances (TBARS) and hydroperoxides formation, cholesterol, triglycerides, free fatty acids and phospholipids, histopathological examination of liver and kidney section of  normal and experimental groups.Results: Oral administration of CFEt and CLEt (0.45 g/kg) aqueous extract and glibenglamide to diabetic rats for 45 days significantly resulted in significant reduction in blood glucose and significant increase in plasma insulin levels. In addition, CFEt at (0.45 g/kg) and CLEt (0.45 g/kg) significantly decreased the levels of serum and tissue lipids as compared to untreated diabetic rats, with significant decrease in thiobarbituric acid reactive substances (TBARS) and hydroperoxides formation in serum, liver and kidney, suggesting its role in protection against lipid peroxidation induced membrane damage.Conclusion: CFEt and CLEt has beneficial effect on plasma insulin and blood glucose level. Moreover it was a prevention of lipid metabolism defects could represent a protective mechanism against the development of atherosclerosis. The CFEt administration showed more effective than CLEt and glibenclamide.